Cine Éden Renascido: Um olhar contemporâneo em meio às ruínas - Saab, Ariel Castro (Brasil, 2024)
The object of this course conclusion work consists of the elaboration of a theoretical study and the conception of a preliminary project intended for the Restoration of the Old Cine Éden, located in the heart of Manaus, with a focus on revitalizing this iconic street cinema.